Prophetic Journalism and Madani Multilateralism: Rebuilding Epistemic Trust in Digital Da'wah - Saragih, M Yoserizal (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The digital information ecosystem in Indonesia and Southeast Asia is increasingly defined by an erosion of epistemic trust, in which religious content, da'wah messaging, and civic discourse circulate through informal, algorithmically mediated networks whose responsibility frameworks remain under-theorized. Existing scholarship on digital journalism has documented the technical and institutional dimensions of this crisis, but has largely proceeded from secular-liberal assumptions that do not directly engage the moral-relational resources already present in Islamic communicative traditions. Using a conceptual, library-based synthesis of Indonesia's prophetic social science tradition, the author's own earlier scriptural analysis of Islamic journalism, and recent Scopus-indexed international scholarship, this article develops Prophetic Epistemic Governance (PEG), a conceptual framework which extends Kuntowijoyo's ilmu sosial profetik and Saragih's (2018) earlier scriptural analysis of Islamic journalism into the domain of digital da'wah governance. PEG integrates four prophetic heuristics, Shiddiq, Amanah, Tabligh, and Fathanah, with two sensitizing constructs, Covenant Density and Verification Latency, and situates them within a wider model of Madani Multilateralism as an alternative to state-centric and platform-centric governance. The article defines Yaumul Marhamah as the ethical horizon to which this system orients, discusses PEG's propositions in relation to recent Scopus-indexed scholarship on digital religious authority, and concludes with a concrete agenda for the empirical research needed to test PEG's propositions in Indonesian and Southeast Asian digital da'wah settings. As a conceptual contribution, this article does not report empirical findings; it offers a theoretical architecture intended to guide such research.